PENDIDIKAN SEXUAL CONSENT PERSPEKTIF TUJUAN PENDIDIKAN NASIONAL DAN PENDIDIKAN ISLAM (Jenis Studi Teks Draft RUU P-KS Tahun 2016 BAB I Pasal 1 Ayat 1) - Ela Hodijah N (STAI Sebelas April Sumedang, 2021)
The discourse on sexual consent material for high school and university students continues the roll, develops, and becomes an interesting conversation. The plan generated a lot of attention and concern from various activists. A scientific study is held to criticize and analyze how good and bad it is if the concept of sexual consent is completely normalized in Indonesia. From this phenomenon, several research problems were formulated to find answers about what sexual consent education is, how to educate on sexual consent from the perspective of national education goals, and the perspective of Islamic education. The research method used a qualitative data approach. A concept analysis of the study of the draft RUU P-KS Bab I Pasal 1 ayat 1 text study as a primary data source and supported by several competent informants and other literacy as a secondary data source. The results of the study, sexual consent is to do sexual activity in a free conscious state without coercion. Sexual consent is not the right solution in solving the problem of crime and sexual violence in society. Sex education needs to be taught to generations, but sexual consent education needs to be rejected. Sexual consent is the core of rejection by various parties because sexual consent is very contradictory to the goals of national education. Sexual education Islamic education perspective is very important to be given ang emphasized on students. In the perspective of Islam education, the fulfillment of sexual needs is the fulfillment of rights and obligations through marriage lawful by Islamic law. There is no sexual consent in Islam, where there is sincerity and sensitivity to understand each other`s physical and psychological condition from a married partner. It is a hope, sexual consent education is not the norm in the Indonesian nation.